Down‐regulation of dual‐specificity phosphatase 6, a negative regulator of oncogenic ERK signaling, by ACA‐28 induces apoptosis in NIH/3T3 cells overexpressing HER2/ErbB2. (27th January 2021) - Kanda, Yuki; Mizuno, Ayami; Takasaki, Teruaki; Satoh, Ryosuke; Hagihara, Kanako; Masuko, Takashi; Endo, Yuichi; Tanabe, Genzoh; Sugiura, Reiko
Abstract: Dual‐specificity phosphatase 6 (DUSP6) is a key negative feedback regulator of the member of the RAS‐ERK MAPK signaling pathway that is associated with cellular proliferation and differentiation. Deterioration of DUSP6 expression could therefore result in deregulated growth activity. We have previously discovered ACA‐28, a novel anticancer compound with a unique property to stimulate ERK phosphorylation and induce apoptosis in ERK‐active melanoma cells. However, the mechanism of cancer cell‐specific‐apoptosis by ACA‐28 remains obscure. Here, we investigated the involvement of DUSP6 in the mechanisms of the ACA‐28‐mediated apoptosis by using the NIH/3T3 cells overexpressing HER2/ErbB2 (A4‐15 cells), as A4‐15 exhibited higher ERK phosphorylation and are more susceptible to ACA‐28 than NIH/3T3. We showed that A4‐15 exhibited high DUSP6 protein levels, which require ERK activation. Notably, the silencing of the DUDSP6 gene by siRNA inhibited proliferation and induced apoptosis in A4‐15, but not in NIH/3T3, indicating that A4‐15 requires high DUSP6 expression for growth. Importantly, ACA‐28 preferentially down‐regulated the DUSP6 protein and proliferation in A4‐15 via the proteasome, while it stimulated ERK phosphorylation. Collectively, the up‐regulation of DUSP6 may exert a growth‐promoting role in cancer cells overexpressing HER2. DUSP6 down‐regulation in ERK‐active cancer cells might have the potential as a novel cancer measure. Abstract : We showed that the NIH/3T3 cells overexpressing HER2/ErbB2 (A4‐15 cells) exhibited high DUSP6 protein levels. ACA‐28 preferentially down‐regulated the DUSP6 protein and proliferation in A4‐15 cells, while it stimulated ERK phosphorylation. DUSP6 down‐regulation mediated by ACA‐28 in ERK‐active cancer cells might have the potential as a novel cancer measure.